Development of Pedagogical Competence Based on Digital Learning for Teacher on Digital Era - Babang Robandi; Ocih Setiasih; Pupun Nuryani; Wawan Setiawardani (Universitas Pendidikan Indonesia, 2022)
The rapid development of the times has an impact on many aspects of life. The education aspect is no exception. Education in the digital era cannot be separated from the implementation of technology in learning. However, the rapid development of technology in Indonesia has not been in line with the development of the ability of educators to implement digital technology in the educational process. This service aims to improve the pedagogic competence of educators in the digital era. The method used in this service activity is through an e-course which has some content that can be accessed by participants within ten days. This service is carried out in the city of Cirebon, but access is opened for educators throughout Indonesia. The results of this activity illustrate that service activities through e-courses are quite effective in improving the competence of educators in the digital era. Of the 160 participants who accessed the learning process to completion, the final score was obtained with an average learning completeness of 85%